Use of event data recorder (EDR) technology for highway crash data analysis - Gabler, Hampton Clay 1954- (Research results digest (National Cooperative Highway Research Program), 2005)
"This digest presents the results of NCHRP Project 17-24 ... This digest is based on a draft final report authored by the principal investigator, Hampton C. Gabler, and Douglas J. Gabauer and Heidi L. Newell, all of Rowan University and Michael E. O'Neill of George Mason Law School."--P. [1]